2022
DOI: 10.3389/fcomm.2021.802596
|View full text |Cite
|
Sign up to set email alerts
|

Nominal Word Order Typology in Signed Languages

Abstract: Although spoken language nominal typology has been subject to much scrutiny, research on signed language nominal word order typology is still a burgeoning field. Yet, the structure of signed languages has important implications for the understanding of language as a human faculty, in addition to the types of universals that may exist across the world’s languages and the influence of language modality on linguistic structure. This study examines the order of nouns and attributive modifiers (adjectives, numerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 89 publications
3
9
0
Order By: Relevance
“…However, it is worth noting that the basic word order bias in Motamedi et al (2022), originally reported by Schouwstra and de Swart (2014), is not regularly observed in the typology of spoken languages (although see Flaherty et al, 2018;Napoli et al, 2017, for evidence in sign languages). Whereas the ordering preferences for adjectives and genitives do seem to be observable in the typology of both spoken and signed languages (Coons, 2022; but see footnote 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is worth noting that the basic word order bias in Motamedi et al (2022), originally reported by Schouwstra and de Swart (2014), is not regularly observed in the typology of spoken languages (although see Flaherty et al, 2018;Napoli et al, 2017, for evidence in sign languages). Whereas the ordering preferences for adjectives and genitives do seem to be observable in the typology of both spoken and signed languages (Coons, 2022; but see footnote 1).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2: Typological counts of the order of nouns with adjective and noun with genitive, in spoken and signed languages (Coons, 2022;Dryer, 2013aDryer, , 2013b Typological data on harmony between these two dependents shows evidence of both types of biases at work: while the two harmonic orders are both well-attested, the non-harmonic order…”
Section: Harmonicmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1960s and 1970s, it has been shown that sign languages of deaf communities are natural languages that can be described by appealing to the levels of structure that characterize spoken languages, such as phonology, morphology, syntax, and semantics/pragmatics (Bellugi & Fischer, 1972; Brentari, 2012; Emmorey, 2002; Johnston & Schembri, 2007; Klima & Bellugi, 1979; Meier, 2002; Sandler & Lillo‐Martin, 2006; Sutton‐Spence & Woll, 1999). In some cases, various aspects of structure can be compared to spoken languages, such as the basic order of subject, verb, and object (Napoli & Sutton‐Spence, 2014), relative clause patterns (Coons, 2022), and split negation (Pfau, 2002), all within the syntactic level of structure.…”
Section: Typical Structures Of Sign Languages and How They Are Acquiredmentioning
confidence: 99%